2002
DOI: 10.1515/epoly.2002.2.1.624
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long chain branching on linear-viscoelastic melt properties of polyolefins

Abstract: Abstract:The aim of this review is to provide evidence that rheological testing is a potent tool for characterising polymers in the melt. An effort has been made in order to gather results in conventional and model polyolefins, and correlating them with phenomena occurring at the molecular level. We have focused our interest on long chain branching (LCB). In the case of materials containing long side-chain branches, strong effects on viscosity, elastic character and activation energy of flow are general featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 129 publications
(263 reference statements)
5
54
0
Order By: Relevance
“…However, the theoretical explanations for LCB detection via rheological techniques from molecular dynamics and models are not discussed here, as this information can already be found in other excellent reviews. [79][80][81] There are also early reviews that report on the aspects of melt rheology for POs, [71] structure and rheology of molten polymers, [81] effects of LCB on linear-viscoelastic melt properties of POs [82] and rheological characterization of LCB. [83] …”
Section: Rheological Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the theoretical explanations for LCB detection via rheological techniques from molecular dynamics and models are not discussed here, as this information can already be found in other excellent reviews. [79][80][81] There are also early reviews that report on the aspects of melt rheology for POs, [71] structure and rheology of molten polymers, [81] effects of LCB on linear-viscoelastic melt properties of POs [82] and rheological characterization of LCB. [83] …”
Section: Rheological Characterizationmentioning
confidence: 99%
“…[82] Such phenomenon becomes more obvious with increased LCBD. Newtonian viscosity regime thus becomes smaller.…”
Section: Zero Shear Viscosity η 0 and Shear Thinning Behaviormentioning
confidence: 99%
“…However, LCB has an enormous impact of rheological properties. It has long been known that the addition of trace amounts of long-chain branching (LCB) produces dramatic changes in the linear and nonlinear rheology [40][41][42][43][44][45]. These well-documented effects include a departure from the "3.4 power law" relating the zero shear viscosity η 0 to the weightaveraged molecular weight, unusually large sensitivity of η 0 to temperature or higher flow activation energies [46], enhanced shear thinning and strain hardening that lead to improved tear resistance, processability, and so forth.…”
Section: 21mentioning
confidence: 99%
“…Obtaining molecular information about LCB using only rheology-based methods is not trivial. Numerous studies reported that increasing the MW, broadening the MW distribution (MWD), or increasing the content of LCB have similar effects on the shear viscosity function [Shroff and Mavridis (1999); Vega et al (2002); Doerpinghaus and Baird (2003); Shroff and Mavridis (1999); van Ruymbeke et al (2005); Stadler and Munstedt (2008b)]. That is, the distribution of relaxation times is not a unique function of chain architecture.…”
Section: Introductionmentioning
confidence: 99%